2014
DOI: 10.1038/tpj.2014.38
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP3A5*3 on kidney transplant recipients treated with tacrolimus: a systematic review and meta-analysis of observational studies

Abstract: The highly variable pharmacokinetics of tacrolimus can hamper the optimal management of kidney transplant patients. This variability has been attributed to the genetic polymorphism of CYP3A5 6986A>G, but the evidence is not clear. We conducted a meta-analysis of studies evaluating the effect of CYP3A5 polymorphism on kidney transplant recipients with tacrolimus plasma concentration divided by daily dose per body weight (C/D) and clinical outcomes. We searched in MEDLINE and EMBASE. We found evidence suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
119
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 57 publications
7
119
1
5
Order By: Relevance
“…The CYP3A5 gene codes for the main metabolic enzyme for tacrolimus, and in the main functional variant, CYP3A5 6986A>G (rs776746), a guanine is substituted for adenine. Carriers of the A allele (AA or AG, CYP3A5 expressers) can produce very high levels of functional CYP3A5 compared with homozygous GG carriers (CYP3A5 non-expressers) [12] . Thus, GG genotype patients need less TAC (high C0/D ratio) to reach the target blood concentration than the A allele carriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CYP3A5 gene codes for the main metabolic enzyme for tacrolimus, and in the main functional variant, CYP3A5 6986A>G (rs776746), a guanine is substituted for adenine. Carriers of the A allele (AA or AG, CYP3A5 expressers) can produce very high levels of functional CYP3A5 compared with homozygous GG carriers (CYP3A5 non-expressers) [12] . Thus, GG genotype patients need less TAC (high C0/D ratio) to reach the target blood concentration than the A allele carriers.…”
Section: Discussionmentioning
confidence: 99%
“…TAC forms a complex with the immunophilin FK-binding protein 12 (FKBP12) and strongly inhibits calcineurin phosphatase activity, IL-2 expression, and subsequently, T-cell activation [7] . Genetic polymorphisms in TAC pharmacokinetic pathways have been widely investigated (www.pharmgkb.org), and it has been confirmed that a single-nucleotide polymorphism, 6986A>G, within intron 3 of the CYP3A5 gene can affect the pharmacokinetics of tacrolimus [5,12] . Recent studies have also shown that TAC pharmacokinetics can be affected by polymorphisms in CYP3A4 (*22, *B, *1G), ABCB1 (2677G>A/T, 1236C>T, 3435C>T), P450 (cytochrome) oxidoreductase (POR) *28, nuclear receptor subfamily 1, group I, member 2 (NR1I2), catechol-O-methyltransferase (COMT), Toll-like receptor 4 (TLR4), and IL-18 [13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that gene polymorphisms, particularly in CYP3A5, affect tacrolimus concentration-dose relationships, so predicting initial dose requirements in lung transplant recipients (32)(33)(34). In kidney transplant recipients, a polymorphism of CYP3A5 was found to be a risk factor for acute rejection and nephrotoxicity (35). Single nucleotide polymorphism analysis of 240 Chinese kidney transplant recipients has revealed a number of other polymorphisms affecting tacrolimus metabolism (36).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically relevant examples of this pharmacogenetic variation have been observed with CYP2C9 (for warfarin) (Cooper et al, 2008;Takeuchi et al, 2009), CYP2C19 (for clopidogrel and omeprazole) (Hou et al, 2014), CYP2D6 (for tamoxifen and codeine) (Madadi et al, 2013;Gryn et al, 2014), and CYP3A5 (for tacrolimus) (Rojas et al, 2015). In some instances, the resulting protein is still functional but exhibits reduced activity (e.g., CYP2C9; Steward et al, 1997); in other cases, the resulting variant protein may be completely devoid of activity or is not expressed (e.g., , such as CYP2D6, CYP2C19, and CYP3A5; Dahl et al, 1992;de Morais et al, 1994;Kuehl et al, 2001, respectively).…”
Section: Introductionmentioning
confidence: 99%